ELABORACIÓN DE UN PLAN DE MARKETING PARA LA EMPRESA ERO$KY AHORRO EN LA CIUDAD DE LOJA - Maldonado Flores, Johanna Maricela (2015)
Marketing and specifically Marketing Plans today are more tools applied by companies of all types and size, because through it you can reach the customer and draw their attention to it decides to purchase a good or service the companies. The commercial companies are among the largest investors in this type of tools nationwide major Supermarkets chains of stores and most used is the way advertising and promotions carried out in order to have the frequency of customers and in turn induce them to buy its products. In local businesses referring to micro-markets, shops cram, stores the main reason that their development is not noticeable in the market and greater coverage to other apply, it is precisely the opposite of the national level, ie, companies do not perform commercial application of competitive strategies, lack of advertising, promotions, customer attracting methods and offer a better price for their product and service quality which in turn led to lower sales of the same and even bankrupting some lack of consumer awareness of their existence in the market, for these reasons and as the company under study is involved in this business field and these problems will be proposed DEVELOPING A MARKETING PLAN NOW FOR SAVINGS ERO$KY Loja, the same as its main focus the company to meet all the lojana citizens through the correct implementation of all detailed here, this plan also It will help the company improve its service at the time of offer and market their products. In addition, it will serve as a tool to reorient the actions in the different processes carried out for the fulfillment of their activities, as well as promote good management of their financial resources to make it a company known for its efficiency 6 and effectiveness by providing development significant to other companies. Marketing Plan consists of the following steps, stages or chapters that were developed:  First is all the description of the subject or title of the thesis which it determined the problems that occurred summarized in the abstract.  The summary is a synthetic way to show part of the problem had  As a third step which we detail Introduction parts because this subject of study was determined.  As a fourth step the theoretical and referential thematic content with what is the Marketing Plan and Company.  Following have methods like:. Descriptive, analytical, scientific, deductive and inductive which allowed the development of the thesis, and the techniques used were direct observation, interviews which were applied to the company manager Ms. Yolanda Flowers and businesses considered competition, surveys of customers in this case also used a population sample of 383 surveys being applied Loja and employees of the company.  In the sixth step all the results obtained through different applied analysis and techniques used to obtain information and their subsequent tabulation and interpretation are.  With the data obtained from the results in this way all the content that leads the Marketing Plan for the company ERO detailed $ KY SAVINGS, which describes each of its strategies and action plans as well as their costs and schedule of activities .  Finally we have the conclusions and recommendations and the company respectively well as a literature foundation and annexes. 7 All this will allow the company ERO $ KY SAVING achieve the desired market positioning Loja, and also become known as a company with excellent products and services offered by it and that consequently their sales increase and is a company with strong profitability. ERO $ KY SAVING is a company that in 5years leading market has achieved an acceptable level of sales and recognition of the people especially the northern sector of the city, but needs to be given an added value that allows expand its market to the entire city as competition is increasing.